The effects of heavy-sled sprint training on acceleration capabilities in female rugby sevens athletes: A pilot study - Sella, F. S.; Beaven, C. M.; McMaster, D. T.; Hebert-Losier, K.; Gill, N. D. (Sport and Exercise Science New Zealand Conference, 2018, 2018)
Well-developed acceleration abilities are critical for performance in rugby sevens. In this pilot study, we investigated the effects of heavy-sled sprint training on acceleration profiles in female rugby sevens athletes. Method Eleven junior female rugby sevens athletes completed 3- weeks of resisted sprint training (5-30m) with heavy sleds (30-85% of body mass). Acceleration performance and biomechanical outputs were computed pre- and post-intervention using the methods described by Samozino et al. Training-induced changes were calculated using effect size (ES) and magnitude-based inferences. Correlations (r) between changes in sprint performance and biomechanical outputs were calculated. Results Small improvements in 5m and 10m times, and changes in mechanical effectiveness of force application (RFmax), force-velocity slope (SFV), and maximum power output (Pmax) were observed (ES = 0.36-0.40). Almost perfect correlations were found between changes in 5m and 10m times with ƒ¢Pmax, theoretical maximum force (ƒ¢F0), and ƒ¢SFV (r .0.92). Discussion Heavy-sled sprint training was likely to improve 5m and 10m times, maximum power, and sprint biomechanics. Specifically, changes in Pmax, F0, and SFV explained over 85% of the variance associated with improvements in 5m and 10m times. Take home message Heavy-sled sprint training is likely to increase acceleration capabilities in female rugby sevens athletes.